Cyberethnography in Primary Education Digitally Mediated Classrooms - Kolokitha, Magdalini; Ventista, Ourania Maria; Arkoumanis, Grigorios; Eleni, Katerina (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
This paper focuses on the methodological choices, obstacles and solutions in our attempt to develop of a methodological framework for cyberethnography, while researching the pedagogical practice in digitally mediated classrooms in primary education. The paper, at large, is an account of our initial attempt to research digitally mediated classrooms. We aim to discuss the notion of cyberethnography both in terms of methodology (Addeo & D'Auria, 2022) and the process followed for the acquisition of access in the digital classrooms. Finally, we will discuss how "fast-tracked" policy implementation and realisation affects not only the act of schooling but also the research around schooling and education, by minimising access and possibilities of research. Theoretically, in this paper we made the choice of using the notion of cyberethnography over the notion of digital ethnography (Delli Paoli, 2022). We use and understand cyberethnography, as an ethnography realised in virtual spaces and digital ethnography as an ethnography that uses digital means. This distinction aims to support a methodological ethnographic research approach in a rapidly digitalised education system.